An administrative justice perspective on improving EIA effectiveness. Issue 2 (3rd March 2020) - Retief, Francois P; Fischer, Thomas B; Alberts, Reece C; Roos, Claudine; Cilliers, Dirk P
ABSTRACT: The aim of this letter is to provide an administrative justice perspective on EIA effectiveness. EIA is described as essentially an administrative instrument, reflecting a number of principles that revolve around an assessment process which should reflect administrative justice. This includes lawfulness, procedural fairness and reasonableness. Consciously and explicitly incorporating these principles into EIA decision-making has significant potential to strengthen EIA effectiveness and making it fit for the twenty-first century.